Optimization of enzymatic hydrolysis conditions for antimicrobial activity against Pantoea spp. causing rice leaf blight - Jamal, Siti Norazura; Lamasudin, Dhilia Udie; Muhialdin, Belal J.; Saidi, Noor Baity; Song, Lai Kok; Yusof, Mohd Termizi (Faculty of Science, Universiti Malaya, 2024)
The Central Composite Design (CCD) within the Response Surface Methodology (RSM) was applied to optimize the enzymatic hydrolysis process. This process used Alcalase® to hydrolyze Bactronophorus thoracites protein with the goal of maximizing its antimicrobial effects. Four distinct parameters were identified as independent variables: pH (A: 8.5–10.5), temperature (B: 45–65 °C), hydrolysis time (C: 120–360 min), and enzyme-to-substrate ratio (D: 1.45%–2.65% w/v). Meanwhile, the antimicrobial activity was chosen as the response variable, specifically against Pantoea ananatis (Y1) and Pantoea stewartii (Y2). According to the findings, the constructed quadratic polynomial model showed a significant correlation with the experimental data, as evidenced by the coefficient of determination (R2) values for antimicrobial activity: Y1 being 0.9893 (p < 0.0001) and Y2 at 0.9848 (p < 0.0001). Optimal antimicrobial activity for Bactronophorus thoracites protein hydrolysates (BTPH) was recorded at 46.748% against P. ananatis and 40.768% against P. stewartii. This result was observed under the optimal conditions of pH 9.5, temperature 55ºC, hydrolysis duration of 240 minutes, and 2.05% w/v enzyme-to-substrate ratio. There was a notable alignment between the actual and predicted values from our models, with the Residual Standard Error (RSE) values falling under 5%. Furthermore, the established Minimum Inhibitory Concentration (MIC) was 250µg/mL, and the Minimum Bactericidal Concentration (MBC) was 500µg/mL for both P. ananatis and P. stewartii. In conclusion, the findings suggest that the refined BTPH has great promise as an effective bioactive component for agricultural use.